Thermal performance of two types of energy foundation pile: Helical pipe and triple U-tube - Zarrella, Angelo; De Carli, Michele; Galgaro, Antonio (Applied thermal engineering, 2013)
When foundation piles are required to deal with a building's stability problems, the installation of a ground source heat pump is a very attractive, cost-effective solution. The pipes of the ground heat exchangers can be buried in the piles and coupled with the heat pump. The heat exchanger pipes can be arranged as a helical coil or U-tubes. This paper conducts a comparative analysis of the helical and triple U-tube configurations inside a foundation pile. A detailed numerical simulation tool was used to conduct the analysis. The problem of heat transfer was solved by means of an equivalent electrical circuit of suitable thermal resistances and capacitances. This paper also looks at a model that uses n-U-tubes inside a bore and takes into account axial heat conduction in the ground and the borehole, as well as the borehole's thermal capacitance. Before use, the detailed numerical simulation tool was compared with field measurements carried out on two energy piles equipped with two different circuits: one helical and one triple U-tube. After tuning, the two circuits were investigated under the same conditions in the short term, and the peak load conditions were analysed. Finally, the influence of the pitch between the turns of the helix was also analysed. •A new model to analyse energy piles with n-U-tubes and helical pipe is presented.•Measurements for energy piles with 3-U-tubes and helical pipe were performed.•The numerical models consider the axial heat conduction in the ground and pile.•The helical pipe provides a better thermal performance than 3-U-tubes.•The pitch between the turns of the helix affects the peak load.